ITKids Part II: Variation of postures and muscle activity in children using different information and communication technologies - Ciccarelli, Marina; Straker, Leon; Mathiassen, S.; Pollock, Clare (IOS Press, 2011)
Objective: There are concerns that insufficient variation in postural and muscle activity associated with use of modern information and communication technology (ICT) presents a risk for musculoskeletal ill-health among school children. However, scientific knowledge on physical exposure variation in this group is limited. The purpose of this study was to quantify postures and muscle activity of school children using different types of ICT. Method: Postures of the head, upper back and upper arm, and muscle activity of the right and left upper trapezius and right forearm extensors were measured over 10–12 hours in nine school children using different types of ICT at school and away-from-school. Variation in postures and muscle activity was quantified using two indices, EVA_{sd} and APDF_{(90-10)}.Results: Paper-based (Old) ICT tasks produced postures that were less neutral but more variable than electronics-based (New ICT) and Non-ICT tasks. Non-ICT tasks involved mean postures similar to New ICT tasks, but with greater variation. Variation of muscle activity was similar between ICT types in the right and left upper trapezius muscles. Non-ICT tasks produced more muscle activity variation in the right forearm extensor group compared to New and Old ICT tasks. Conclusion: Different ICT tasks produce different degrees of variation in posture and muscle activity. Combining tasks that use different ICT may increase overall exposure variation. More research is needed to determine what degree of postural and muscle activity variation is associated with reduced risk of musculoskeletal ill-health.